Silencing of Antichondrogenic MicroRNA-221 in Human Mesenchymal Stem Cells Promotes Cartilage Repair In Vivo. (27th March 2016) - Lolli, Andrea; Narcisi, Roberto; Lambertini, Elisabetta; Penolazzi, Letizia; Angelozzi, Marco; Kops, Nicole; Gasparini, Simona; van Osch, Gerjo J.V.M.; Piva, Roberta
Abstract: There is a growing demand for the development of experimental strategies for efficient articular cartilage repair. Current tissue engineering-based regenerative strategies make use of human mesenchymal stromal cells (hMSCs). However, when implanted in a cartilage defect, control of hMSCs differentiation toward the chondrogenic lineage remains a significant challenge. We have recently demonstrated that silencing the antichondrogenic regulator microRNA-221 (miR-221) was highly effective in promoting in vitro chondrogenesis of monolayered hMSCs in the absence of the chondrogenic induction factor TGF-β. Here we investigated the feasibility of this approach first in conventional 3D pellet culture and then in an in vivo model. In pellet cultures, we observed that miR-221 silencing was sufficient to drive hMSCs toward chondrogenic differentiation in the absence of TGF-β. In vivo, the potential of miR-221 silenced hMSCs was investigated by first encapsulating the cells in alginate and then by filling a cartilage defect in an osteochondral biopsy. After implanting the biopsy subcutaneously in nude mice, we found that silencing of miR-221 strongly enhanced in vivo cartilage repair compared to the control conditions (untreated hMSCs or alginate-only). Notably, miR-221 silenced hMSCs generated in vivo a cartilaginous tissue with no sign of collagen type X deposition, a marker of undesired hypertrophic maturation. Altogether our data indicate that silencing miR-221 has a prochondrogenic role in vivo, opening new possibilities for the use of hMSCs in cartilage tissue engineering.